I Mind Map Application Needs Analysis to Improve Students’ Mathematical Concept Understanding Ability - Uun Pertiwi; Nanang Khuzaini; Beneditha Beneditha; Angeline Cristin; Felicya Clara (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2022)
The ability to understand concepts is the mastery of the material in which students recognize, know, and are able to re-express concepts in a form that is easier to understand. However, students’ conceptual understanding skills still tend to be low. So it takes teaching materials that integrate these abilities. For this reason, this study aims to analyze the need for teaching materials based on mind map applications to improve students’ conceptual understanding skills. A mind map is a mind map in the form of a diagram that visually describes ideas, concepts, information, or other things. This type of research is descriptive qualitative. The research was conducted in one of the public junior high schools in Yogyakarta. The subjects in this study were 32 students of class IXA. Data collection techniques used interviews, concept understanding ability tests, and preliminary study questionnaires. While the data analysis technique uses the Miles and Huberman model which consists of data collection, data reduction, data presentation, and drawing conclusions. The results showed that teachers had not implemented mind map-assisted learning, students’ conceptual understanding abilities tended to be low, students were interested in learning using mind map applications because students could develop ways of thinking and make them more active during learning